2019
DOI: 10.1029/2019gl085369
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical Energy of Return Strokes: A Comparison Between a Statistical Model and Measurements

Abstract: This letter proposes a new statistical model of thunder. The tortuous geometry of the emitting return stroke is randomly generated to fit observations of negative cloud-to-ground discharges. Pressure waves are initialized by radiation-hydrodynamics simulations and linearly propagated into an isothermal atmosphere incorporating standardized sound absorption. The thunder pressure frequency signal is defined as the product of the input pressure governed by a deposited energy with the stochastic frequency response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
14
1
7
Order By: Relevance
“…Studies about thunder, since the 1960s, have been dedicated to the theoretical interpretation of thunder generation (whether in the audible or infrasonic domain) and to the possibility of reconstructing the acoustic sources of thunder in three dimensions. Lacroix et al [3] have pointed out that arrays having an aperture in the kilometer range prevent precise 3D reconstruction; furthermore, Farges et al [4] showed that beyond 20 km it is not possible to reconstruct in 3D the lightning channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about thunder, since the 1960s, have been dedicated to the theoretical interpretation of thunder generation (whether in the audible or infrasonic domain) and to the possibility of reconstructing the acoustic sources of thunder in three dimensions. Lacroix et al [3] have pointed out that arrays having an aperture in the kilometer range prevent precise 3D reconstruction; furthermore, Farges et al [4] showed that beyond 20 km it is not possible to reconstruct in 3D the lightning channels.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic sources are co-localized with the discharges located using the electromagnetic measurements of a lightning mapping array (LMA). Very recently, Lacroix et al [3] suggested a new model based on Few's [9] development, which also takes into account the interference of the waves emanating from the multiple sources distributed along the flash channel. The authors showed that the amplitude level of the infrasonic part of the signal is thus comparable with or even higher than the audible one.…”
Section: Introductionmentioning
confidence: 99%
“…It should be, however, noted in this respect that the analysis was limited on the localization of the region (point) from which the highest infrasound power was generated to different directions because only time instants of the most distinct pressure fluctuations were used for the calculations of source positions. As mentioned previously, the pressure fluctuations at different microbarometer sites were not sufficiently correlated to imagine the whole lightning channel as was done by Lacroix et al (2019) who used the small-scale array. Nevertheless, the localizations of the highest infrasound source power mostly to altitudes 3-5 km in this study are consistent with some previous studies that used small scale arrays and focused on the analysis of distinct short infrasound pulses (Chum et al, 2013;Arechiga et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of the not fully explained phenomena is also the generation of acoustic pulses in the infrasound frequency range that are observed in addition to the audible thunderclap. According to recent works, the source of infrasound is fast adiabatic expansion of the hot lightning channel as it is generally accepted for audible frequency range (Few, 1969;Assink et al, 2008;Lacroix et al, 2019). Another mechanism could be the pressure change caused by ohmic air heating by currents flowing from the charged area into the lightning channel (Few, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Co-localisation of acoustic sources with in-cloud detections provided by SAETTA high-frequency (60-66 MHz) electromagnetic lightning locating system, and with ground impacts provided by Meteorage, ensures the efficiency and precision of the method. This one was already used successfully in a previous field campaign (HyMeX-SOP1) in Cévennes in 2012 [2,3,4]. The detection algorithm PMCC also provides the various recorded signal intensities.…”
Section: Acoustical Reconstruction and Thunder Energy Localisation In Lightning Flashes Measured Over Corsica During Exaedre Field Campaimentioning
confidence: 99%